Use of the mind mapping learning model to improve the ability of students writing fantasy story text - Alna Royani; Yessi Fitriani; Darwin Effendi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to see the ability to write fantasy stories in Indonesian language learning with the mind mapping model of class VII-2 students at SMP Negeri 13 OKU in the 2020/2021 academic year. The approach used is a quantitative approach. This type of research is descriptive research. The data analysis in this study is the result of the assessment of student work, namely 2 assessors, namely assessor 1 and assessor 2 accompanied by an average. The results showed that the implementation of teacher learning was going well. Based on the research results, it can be concluded that the ability to write fantasy stories using the Mind Mapping model is in the ability category. Suggestions for this research are 1) so that grade VII students can improve their writing skills to get better results. 2) so that teachers of SMP Negeri 13 OKU can use an easy and precise learning model in the learning process. 3) so that other researchers can use this thesis as a reference source.